Compare the Mean Change in Homeostatic Model Assessment (HOMA) Index in Polycystic Ovarian Syndrome Patients Treated with Myoinositol Versus Metformin (Medical Forum Monthly, 2023)
Objective: To compare the mean change in homeostatic model assessment (HOMA) index in polycystic ovarian syndrome patients treated with myoinositol versus metformin presenting in a tertiary care hospital.Study Design: Randomized Controlled trial study.Place and Duration of Study: This study was conducted at the Gynaecology unit IV, Fatima Memorial Hospital, Lahore for six months after approval of synopsis i.e. from 29th August 2018 to 29th January 2019.Materials and Methods: Sample size of 150 cases (75 in each group) was included through Non-Probability consecutive sampling technique after the approval from hospital ethical committee. All the patients were followed up monthly for 6 months on OPD basis to check compliance and any side effects and HOMA after 6 months of treatment was calculated again for the patients.Results: The mean age of the patients was noted 27.30 ± 7.82 years in the myoinositol group and 27.13 + 7.43 years in the metformin group (P-value = 0.890). There were no significant intergroup differences found in the age groups. The mean body mass index was calculated to be (27.48 ± 2.61 vs 27.04 + 2.43) in myoinositol and metformin groups respectively. HOMA-IR values decreased from 4.00 ± 0.69 to 2.36 ± 0.61 & 3.96 ± 0.69 to 3.50 ± 0.60 in group A & B respectively over a period of 6 months. Statistically significant difference was observed among both groups in terms of mean change in HOMA-IR.Conclusion: The growing interest toward the clinical effects of myoinositol is witnessed by the recent analysis which demonstrated how this supplement is effective in decreasing HOMA-IR in patients with PCOS. Through the results of the current study we concluded that MI and metformin improves the metabolic profile of women with PCOS, when supplementation lasted at least 6 months.